Developing English Public Speaking Learning Materials for Dentistry Department Students in Yogyakarta - Pradana Akbar Tanjung; Ashadi (Epistema, 2026)
This study aims to develop English public speaking materials for dentistry students using a design-based research approach guided by Branch’s ADDIE model (2009). The participants were students from a private institution in Yogyakarta selected through purposive sampling. Data were collected through questionnaires, field notes, and semi-structured interviews. The developed materials are categorized as English for Specific Purposes (ESP) and were developed based on Nunan’s (2004) Task-based Language Teaching (TBLT) framework. The needs analysis shows that dentistry students require English resources to improve their public speaking skills. Expert evaluations of the developed materials scores between 3.50 and 3.75, placing them in the “very good” category. Try-out results also showed “very good” scores, ranging from 3.36 to 3.52. Field notes from two implementation cycles indicate slight improvements in motivation, engagement, and group collaboration. Students’ mean scores increased from 7.94 in the pre-test to 8.11 in the post-test. Overall, the findings suggest that the developed materials are valid and effective in supporting students’ public speaking development. Keywords: ESP, public speaking, TBLT, English education, dentistry